Nonlinear effects of humidex on risk for asthenopia among adults: a national cross-sectional survey in China - Xiaotian Wu; Xin Chen; Fuyue Tian; Maoyuan Yang; Fan Lu; Ruzhi Deng; Na Lin (Frontiers in Public Health)
IntroductionThe health effects of ambient humidity and temperature are well-established. However, few studies have investigated the relationship between humidity, temperature, and asthenopia. Our goal was to quantify the impact of humidity and temperature on the likelihood and severity of asthenopia among adults in China.MethodsWe conducted a national cross-sectional online survey from June 2020 to March 2022, involving 48,000 adults aged 18 and older from 31 provinces in China. City-level meteorological data, including daily average temperature and relative humidity, were obtained from the China Meteorological Data Network. The humidex was used as the exposure indicator. Asthenopia was self-reported using the 17-item Asthenopia Survey Questionnaire. Covariates included age, gender, season, geographic region, presbyopia status, history of eye surgery, average daily duration of near vision activities, daily sleep duration, sleep quality, and frequency of heightened anxiety or depression. The generalized estimation equation model was used to analyze the associations between humidex and asthenopia.ResultsOf the 34,303 adults who completed the survey, 38.8% reported asthenopia. Among these, 17.1% were mild, 18.5% were moderate, and 3.2% were severe. The average humidex of the past 2 weeks (range − 28.25 to 45.75°C, mean 25.07 ± 14.26°C) was positively correlated with the likelihood (OR: 1.005, 95% CI: 1.003–1.006, p-value <0.001) and severity (OR: 1.004, 95% CI: 1.003–1.006, p-value <0.001) of asthenopia. The associations between the average humidex of the past 1 month or 1 year and asthenopia were consistent with the past 2 weeks. Additionally, a nonlinear J-shaped relationship was observed between humidex and asthenopia prevalence and severity: low, high, and very high humidex were identified as risk factors for asthenopia.ConclusionBoth high (≥30°C) and low (<10°C) humidex levels were associated with higher likelihoods and severity of asthenopia in adults. The influence of meteorological factors such as humidity and temperature on asthenopia should not be overlooked.